2015
DOI: 10.1039/c5tc01208b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh photo-responsivity and detectivity in multilayer InSe nanosheets phototransistors with broadband response

Abstract: We demonstrate the strategies and principles for the performance improvement of layered semiconductor based photodetectors using multilayer indium selenide (InSe) as the model materials. It is discovered that multiple reflection interference at the interfaces in phototransistor device leads to thickness-dependent photo-response, which provide a guideline to improve the performance of layered semiconductor based phototransistors. The responsivity and detectivity of InSe nanosheets phototransistor can be adjusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
157
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(166 citation statements)
references
References 33 publications
7
157
2
Order By: Relevance
“…We found that the photoresponsivity reaches to its maximum value of ~ 51 AW -1 at an illumination intensity P eff = 63.3 nW when operating in the ON state (V g > 0 V). This value is significantly higher than the previously reported other III-VI group and other Se based 2D materials [14,15,21,22,[32][33][34][35][36][37][38][39][40].…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…We found that the photoresponsivity reaches to its maximum value of ~ 51 AW -1 at an illumination intensity P eff = 63.3 nW when operating in the ON state (V g > 0 V). This value is significantly higher than the previously reported other III-VI group and other Se based 2D materials [14,15,21,22,[32][33][34][35][36][37][38][39][40].…”
Section: Resultscontrasting
confidence: 52%
“…Mudd et al [13] demonstrated that exfoliated InSe nano-sheets, show a crossover from a direct to an indirect band gap, when the flake thickness is reduced to a few nanometers. Similarly, studies also indicate that photo response in multilayer InSe nano-sheet based phototransistor increases with increasing number of layers and attains a maximum value, (in this [14] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Introductionmentioning
confidence: 99%
“…The most attracting properties are its lighter electron mass (m * =0.143 m 0 ) [6] and high electron mobility of 10 3 cm 2 V -1 s -1 . Recently, our and others studies reveal that thin-film InSe is a promising material for high performance electronic and optoelectronic devices [7][8][9][10]. The mobility of multilayer InSe FETs is up to 10 3 cm 2 V -1 s -1 due to suppressed carrier scattering from dielectric substrate [7].…”
mentioning
confidence: 98%
“…The mobility of multilayer InSe FETs is up to 10 3 cm 2 V -1 s -1 due to suppressed carrier scattering from dielectric substrate [7]. Furthermore, few-layered InSe photodetector shows a high responsivity [9] and gatetunable behavior [10], making promising application in photodetection. However, the early studies still focus on multilayer or thin-film (10 nm) [7][8][9][10], atomically thin InSe is been ignored.…”
mentioning
confidence: 99%
“…Besides graphene-based heterojuctions, p-n junctions provide another platform to improve photoresponse [80]. As we know, p-n junctions are the basic building blocks of many optoelectronic devices, which have been utilized for rational control of their fundamental parameters, such as the bandgap, mobility and effective mass of charge carriers.…”
Section: Hybrid Semiconductor Materials With P-n Junctionsmentioning
confidence: 99%